Qual é a dança do IAdança? - Godoy, Kathya Maria Ayres de [UNESP]; Faria, Ítalo Rodrigues [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
The IAdança - Dance Group of UNESP Art Institute was established in 2005 and aims to develop and present research in contemporary dance focusing on processes of creating, training and scientific artistic research. The creative process generates choreographic works that make up the group's repertoire and are presented in cultural events. Through a selection process (interviews, availability, profile), undergraduates (the bachelor's degree in art and in different languages), graduate, teachers and researchers, both UNESP and other institutions and the community, have been or are part of the group. As articulates the actions of the Dance Research Group, Aesthetics and Education - GPDEE, developing collective and individual research projects, produces scientific works, the result of reflection of its members, both in theoretical format as in audiovisual artistic production (video dance, production and three publishing digital books, etc.) and organizes scientific cultural artistic events. In this sense promotes awareness and public education in artistic and educational area.

O IAdança – Grupo de Dança do Instituto de Artes da UNESP foi criado em 2005 e objetiva desenvolver e apresentar pesquisa em dança contemporânea com foco nos processos de criação, formação e investigação artística científica. O processo criativo gera obras coreográficas que compõem o repertório do grupo e são apresentadas em eventos culturais. Através de processo seletivo (entrevistas, disponibilidade, perfil), alunos de graduação (dos cursos de bacharelado e licenciatura em arte nas diferentes linguagens), pós-graduação, professores e pesquisadores, tanto da UNESP como de outras instituições e comunidade, fizeram ou fazem parte do grupo. Como se articula as ações do Grupo de Pesquisa Dança, Estética e Educação – GPDEE, no desenvolvimento projetos coletivos e individuais de pesquisa, produz trabalhos científicos, fruto da reflexão de seus integrantes, tanto em formato teórico como em produção artística audiovisual (videodança, produção e publicação de três livros digitais, etc) e organiza eventos artísticos culturais científicos. Nesse sentido promove a difusão e formação de público na área artística e educacional.
Keywords: Dance; Cultural action; Processes of creating; Dança; Ação cultural; Processo de criação